Impact of Fixed and Dynamic Factors on Cognitive Ability in Epilepsy - Sultonova Dilbar Azamat qizi.; Azizova R.B. (Zien Journals, 2023)
Epilepsy is a major public health problem. Several studies suggest a significant influence of epilepsy and its treatment on the dynamic and functional properties of brain activity. Epilepsy can affect mental development, cognition and behaviour. Patients with epilepsy may have reduced intelligence, attention and problems with memory, language and frontal executive functions.
Keywords: Cognition; epilepsy; mechanisms